Assessment of natural radioactivity and radon release potential of Silurian black shales - Crowley, Quentin (My University, 2024)
Many countries are developing a radon action plan to provide decision-makers with a reliable tool for reducing the harmful effects of radon exposure in dwellings and among the general public and, accordingly, to implement land development strategies. Mapping the geogenic radon release in different geological environments could assist in delineating areas that require priority monitoring and regulation, as well as applying radon reduction techniques in newly constructed buildings. In this paper, the activity concentration of 238U, 226Ra, 232Th and 40K and the exhalation rate of 222Rn have been estimated for the Silurian black shales of Villasalto, a district in the south-eastern Sardinia (Italy). The radioactivity of 226Ra, 232Th and 40K radionuclides was found relatively high (256.32 ± 87.00 Bq.kg−1), low (44.16 ± 9.47 Bq.kg−1) and moderate to high (856.28 ± 392.41 Bq.kg−1) respectively. The radon emanation coefficient (E) and the radon production rate (PRn) have been calculated based on the analysis of the radon growth model inside a sealed chamber. E was found to correlate well with the activity concentration of 226Ra, as well as with the grain size of the soil/rock samples under investigation. PRn was relatively high, ranging from 212.54 to 524.27 Bq.m−3.h−1. Furthermore, the mean value of the main radiation hazard indexes (i.e., the radium equivalent activity, the outdoor gamma-ray dose rate and the annual eﬀective dose) were found to be 299.07 ± 138.62 Bq.kg−1, 169.97 ± 75.58 nGy h−1 and 0.21 ± 0.09 mSv.y−1 respectively.
PUBLISHED
Keywords: Terrestrial radiation; Geogenic radon potential; Human exposure; Health risk; Smart & Sustainable Planet; RADON; gamma radiation